A Novel Green MIP-202/TOCNF Composite Aerogel for Rapid PFAS Adsorption: Performance, Kinetics, and Mechanistic Insights - Muhammad Hamza; Muhammad Waqas; Islam Elsayed; Gregory Schueneman; El Barbary Hassan (Journal of Environmental Chemical Engineering, 2026)

Biological effects of statins in systemic sclerosis: a systematic review and meta-analysis of 323 patients - Mostafa A. Khalifa; Hamzah M. Alghzawi; Shehabeldin S. Anan; Ahmad Al Rifai; Ayah A. Anwar; Hayder Ali Raheem Al-Saedi; Eman Awady; Islam Masood; Mohamed Elsayed Badr; Mohamed Ismail; Obada Muayaid; Omar M. Ahmed; et al. (DARU Journal of Pharmaceutical Sciences, 2026)

Mitigating surface industrial heat island effects in arid environments: A machine learning approach to sustainable planning - Islam M. Hamdi; Eman Albalawi; Elsayed K. AbdAlmapoed; Sayed R. AbdElaal (Energy and Buildings, 2026)

Bridging food and clinical neurotherapeutics in ADHD management: A comprehensive comparative evidence on phytochemicals and non-pharmacologic paradigms - Eman Maher Zahran; Aliaa Gamal; Motaz M. Hassan; Mohamed M. Elsayed; Eyad Y. Elhamadany; Nursin Mustafa Bayoumi; Tarek Gamal Ebrahim; Fatma Alzahraa Mokhtar; Islam M. Abdel-Rahman; Hesham A. Abou-Zied; Usama Ramadan Abdelmohsen (Food Bioscience, 2026)

Investigation of the Antibacterial Effectiveness of Hybrid Recombinant Bacteriocins Circular Enterocin and Pyocin L1 Derived from Pseudomonas aeruginosa and Enterococcus faecalis - Lina Jamil Abdel-Hafez; Mohamed Salah Basiouny; Islam Yousif Mostafa; Rehab Moustafa; Khaled Abuelhaded; Haytham Mohamed Abd-Elhalim; Abanoub A. S. Shaker; Hassan Elsayed; Olfat Salem; Amir Mahfouz Mokhtar Sarguos; Ahmed Hassan Ibrahim Faraag (Biochemical Genetics, 2026)

Biochemical and histological alterations induced by florpyrauxifen-benzyl herbicide in Nile tilapia (Oreochromis niloticus) - Noura Nabet; Elsayed A. Khallaf; Alaa Alnenaey; Islam M. El-Garawani; Esraa Hanafy; Nasr Khalil; Amany E. Nofal (Environmental Science and Pollution Research, 2026)

Ferric Carboxymaltose Among Patients with Heart Failure and Iron Deficiency: An Updated Meta-Analysis of Randomized Controlled Trials - Ahmed Elmorsy Mohamed; Ahmed Farid Gadelmawla; Zeyad Kholeif; Elsayed Balbaa; Ameer Awashra; Mohamed Elnady; Ahmed Diaa; Mohab Elnashar; Haytham A. M. Dwaik; Eman Mohyeldin; Ranem Afify; Rana Rashwan; et al. (Cardiovascular Toxicology, 2026)

Evaluation of lactoferrin administration as an antibiotic alternative growth promoter: impacts on rabbit’s growth, meat quality, blood biochemical parameters, immune status, antioxidant status, and tissue histology - Tharwat A. Imbabi; Shimaa A. Amer; Eman H. Halawa; Islam I. Sabeq; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Shimaa N. Edris; Simon J. Davies; Lamiaa M. El-Maghraby; Abdalla El-Hadary; Ebrahim Elkhtab; Mohamed H. Abdel Aal; et al. (Tropical Animal Health and Production, 2025)

The impacts of novel lyophilized milk fermented with potential probiotic Lactobacillus sp. on the physiological indicators, meat characteristics, blood parameters, and gene expression in weaned rabbits - Ebrahim Elkhtab; Ali Osman; Rania M. Y. Heakel; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Ahmed A. Aly; Mohamed H. Abdel Aal; Islam Sabeq; Shimaa A. Amer; Simon J. Davies; Tharwat A. Imbabi (Tropical Animal Health and Production, 2025)

Chrysin-loaded poly (lactic-co-glycolic acid) nanoparticles alleviate sepsis-induced splenic injury by regulating myeloid-derived suppressor cells - Islam Ahmed Abdelmawgood; Abeer Mahmoud Badr; Asmaa Elsayed Abdelkader; Noha A. Mahana; Ayman Saber Mohamed; Hadeer Hesham Abdelfattah (Immunologic Research, 2025)

Assessment of urban heat island effects in industrial areas of Egypt using robust statistical methods - Islam Hamdi; Elsayed K. AbdAlmapoed; Sayed R. AbdElaal (Remote Sensing Applications: Society and Environment, 2025)

The induced hepatotoxicity and genotoxicity in Oreochromis niloticus exposed to a newly released florpyrauxifen-benzyl herbicide - Noura Nabet; Elsayed A. Khallaf; Alaa Alne-na-ei; Islam M. El-Garawani; Rehab G. Elgendy; Esraa Hanafy; Nasr Khalil; Heba M. R. Hathout (Ecotoxicology, 2025)
The investigation of the toxic potential of a newly introduced herbicide, Florpyrauxifen-benzyl (FPX), on Nile tilapia ( Oreochromis niloticus ) was the aim of this study. For 96 h, the median lethal concentration (LC 50 ) was assessed in fish juveniles using the Probit analysis following the exposure to five concentrations of FPX (2–3 ppm). For investigating some mechanisms of FPX toxicity, fish were allocated into three groups (0, 0.27 and 0.54 ppm of FPX) and the cut-off intervals of the exposure were at 7 and 15 days. Liver malondialdehyde (MDA) and reduced glutathione (GSH) levels were assessed. In addition, superoxide dismutase (SOD) and catalase (CAT) were evaluated at both of transcriptional and enzymatic activity levels. Histopathological effects on the liver and erythrocytic nuclear abnormalities (ENAs) were monitored too. The 96h-LC 50 was found to be 2.61 ppm, revealing the toxic potential of the FPX on Nile tilapia. Concentrations of FPX induced oxidative stress in fish by altering activities of antioxidant enzymes and their transcripts. The genotoxic effect of FPX was evidenced by a significant ( P < 0.05) increase in micronuclei (MNs) and ENA frequencies. Significant liver histopathological alterations were observed at both FPX concentrations, with the highest effects at a concentration of 0.54 ppm FPX. Results suggest that FPX may exert oxidative, genotoxic, and histopathological effects on non-targeted species such as Nile tilapia if it is used improperly. Although fish could be used as an indicator for toxic materials in the aquatic habitat, future studies on other organisms, FPX concentrations or durations are recommended.

Acetamiprid-induced pulmonary toxicity via oxidative stress, epithelial-mesenchymal transition, apoptosis, and extracellular matrix accumulation in human lung epithelial cells and fibroblasts: Protective role of heat-killed Lactobacilli - Samah S. Arafa; Heba A. Elnoury; Sahar Badr El-Din; Mohamed A. Sakr; Fatma Fawzi Hendawi; Rehab Ali Elsayed Masoud; Samia Soliman Barghash; Doaa Sabry Elbehairy; Ayat Abdelaty Hemeda; Islam Mostafa Farrag; Doaa Sayed Abdelrahman; Amira Mohammad Elsadek; et al. (Food and Chemical Toxicology, 2025)

Upcycling of industrial pea starch by rapid spray nanoprecipitation to develop plant-derived oil encapsulated starch nanoparticles for potential agricultural applications - Rahul Islam Barbhuiya; Charles Wroblewski; Sivaranjani Palanisamy Ravikumar; Guneet Kaur; Winny Routray; Jayasankar Subramanian; Abdallah Elsayed; Ashutosh Singh (Carbohydrate Polymers, 2024)

The role of marine bacteria in modulating the environmental impact of heavy metals, microplastics, and pesticides: a comprehensive review - Islam I. Teiba; Emad H. El-Bilawy; Ibrahim A. Abouelsaad; Akram Ismael Shehata; Mayada Alhoshy; Yusuf Jibril Habib; Nermeen M. Abu-Elala; Nagwa EL-Khateeb; Elsayed B. Belal; Warda A. M. Hussain (Environmental Science and Pollution Research, 2024)

Analysis of potential genes, immunological and antioxidant profiles associated with trypanosomiasis susceptibility in dromedary camels - Ahmed A. Elsayed; Safaa M. Barghash; Adel M. El-Kattan; Islam M. Wassif; Wafaa A. Osman; Ahmed I. Ateya (Veterinary Parasitology, 2024)

Fatigue life and behaviour of ribbed GFRP reinforced concrete beams - Islam Elsayed Nagy; Alireza Asadian; Khaled Galal (Engineering Structures, 2024)

A review of nanoparticle synthesis and application in the suppression of diseases in fruits and vegetables - Rahul Islam Barbhuiya; Natalia Nevarez Tinoco; Saipriya Ramalingam; Abdallah Elsayed; Jayasankar Subramanian; Winny Routray; Ashutosh Singh (Critical Reviews in Food Science and Nutrition, 2024)

Evaluation and performance comparison of different models for global solar radiation forecasting: a case study on five cities - Mohamed A. Ali; Ashraf Elsayed; Islam Elkabani; M. Elsayed Youssef; Gasser E. Hassan (Environment, Development and Sustainability, 2023)
Recently, solar energy has emerged as the most promising renewable energy source to meet the world’s energy demands. However, to harness the potential of solar energy, accurate data on solar radiation are crucial. It is considered the first step in assessing solar resources for various applications and achieving energy sustainability goals. Due to the unavailability of solar radiation measurements in many parts of the world, several models have been developed to predict global solar radiation (GSR) at these locations. Thus, this study aims to evaluate the proficiency of several GSR models at five new locations and determine the most suitable one for GSR prediction. The study has further developed solar radiation models for these new locations, as well as general ones for the entire region, which does not have any GSR models despite the existence of many planned solar energy facilities in this area. Additionally, the study investigates the effect of changing the length of the validation dataset on models’ performance and accuracy, as well as assesses the introduced models’ generalization capability. To achieve these objectives, the observed data of GSR for approximately 37 years at studied locations are used to develop and validate the proposed models. The study’s findings reveal that Model 1 provides the best performance at all locations, with accuracy, coefficient of determination ( $$R^{2}$$ R 2 ), ranging from 95 to 98%, except for the coastal location, where it is from 91 to 95%. The remaining performance indicators of the best models, such as RMSE, MABE, MAPE, and $$r$$ r , are good, and their values range from 0.7863 to 1.9097 (MJ m −2 day −1 ), from 0.6430 to 1.7060 (MJ m −2 day −1 ), from 3.4319 to 10.0890 (%), and from 0.9914 to 0.9981, respectively. The length of the validation dataset has a slight effect on the models’ performance, ranging from about 1% to 2%. Therefore, Model 1 is the recommended solar radiation model, which can provide precise and rapid estimates of global solar radiation. This approach could be used in the design and performance evaluation of many solar applications. The primary benefit of this approach in the current investigation is that temperature data are continuously and effortlessly recorded for various purposes.

Towards achieving university sustainability! Linking social responsibility with knowledge sharing in Saudi universities - Afroze Nazneen; Islam Elgammal; Zubair Rashid Khan; Muhammad Haroon Shoukat; Ali Elsayed Shehata; Kareem M. Selem (Journal of Cleaner Production, 2023)

Soil and foliar applications of zinc sulfate and iron sulfate alleviate the destructive impacts of drought stress in wheat - Md. Abdul Mannan; Mahmuda Akter Tithi; M. Rafiqul Islam; Md. Abdullah Al Mamun; Shamim Mia; Md. Zillur Rahman; Mohamed F. Awad; Abdelaleim I. ElSayed; Elsayed Mansour; Md. Sazzad Hossain (Cereal Research Communications, 2022)

The Effect of Neonicotinoids Exposure on Oreochromis niloticus Histopathological Alterations and Genotoxicity - Islam M. El-Garawani; Elsayed A. Khallaf; Alaa A. Alne-na-ei; Rehab G. Elgendy; Hassan M. Sobhy; Adel Khairallah; Heba M. R. Hathout; Farag Malhat; Amany E. Nofal (Bulletin of Environmental Contamination and Toxicology, 2022)
This study aimed to examine the side effects of selected neonicotinoids (Acetamiprid, Aceta, and Imidacloprid, Imid) on Oreochromis niloticus juveniles. The acute toxicity, Probit method, revealed an LC 50 of 195.81 and 150.76 ppm for Aceta/96 h and Imid/72 h respectively. The fish were divided into three groups that were exposed, for 21 days (n = 5/replicate), to 1/10 of the LC 50 of either neonicotinoids, however, the third was an unexposed control group. Results of erythrocytic micronucleus (MN), and nuclear abnormalities (NA) showed that Aceta and Imid exposure caused a significant ( p < 0.05) increase in MN by ~ 2.2 and ~ 10 folds, respectively relative to control. NAs occurred at the order of kidney-shaped > budding > binucleated in Aceta, however, budding > binucleated > kidney-shaped was noticed in the Imid group. Histopathological changes in gills, liver, and muscles were observed significantly in both exposed groups with more severity in the Imid group. Collectively, Aceta and Imid have potential genotoxicity and histopathological alterations in O. niloticus .

Towards fairly sharing risks in public-private partnership projects: Shapley value approach - Fatma Mostafa; Ahmed M. Elsayed; Mohamed S. Eid; Emad Elbeltagi; Islam Elmasoudi (Innovative Infrastructure Solutions, 2022)